Hypogonadism is independently associated with varicocele repair in a contemporary cohort of men in the USA - Cailey Guercio; Dattatraya Patil; Akanksha Mehta (Asian Journal of Andrology, 2019)
We aimed to identify demographic and clinical predictors of varicocele repair in a contemporary cohort of men in the USA. We queried the 2009–2015 MarketScan Database using relevant ICD9, ICD10, and CPT codes to identify all 18–45 year olds with varicoceles. Differences in age, area of residence, clinical characteristics, and medical management between men who did and did not undergo varicocelectomy (open, laparoscopic, or microsurgical) during the study period were compared using unpaired t-tests and Chi-squared tests for continuous and categorical variables, respectively. Multivariable logistic regression analysis was used to evaluate age, semen analyses, and serum hormone assessment as predictors of varicocele repair. SAS version 9.4 was used for all statistical analyses. Significance was set at P < 0.05. Approximately 40% of men with varicoceles underwent repair, primarily through an open approach. Men who underwent repair were more likely to have a diagnosis of male infertility (15.5% vs 7.9%, P < 0.001) and male hypogonadism (3.4% vs 0.9%) and were more likely to complete semen analyses (36.1% vs 12.2%, P < 0.001) and serum testosterone evaluation (42.5% vs 18.8%, P < 0.001). In multivariable regression models, the strongest predictors of varicocele repair were semen analysis (OR = 2.78, 95% CI: 2.56–3.02), age 18–25 years (OR = 2.66, 95% CI: 2.36–2.98), and serum testosterone evaluation (OR = 1.67, 95% CI: 1.51–1.86). Although male infertility remains the most important indication for varicocele repair, male hypogonadism is emerging as an independent predictor of varicocelectomy, which may represent a change in the clinical management of varicoceles in the USA.